The potential effects of the social costs from alcohol consumption on state financial condition. Issue 1 (5th March 2018) - Hummel, Daniel
Abstract : Purpose: Most of the literature on the topic of alcohol consumption and externalities related to it identify adverse effects. The effects of these possible externalities on government financial condition remain relatively unexplored in the literature. In economics, the theory of social costs related to unrestricted economic behavior such as alcohol consumption has been explored since the early twentieth century which spread into the field of public administration through welfare economics. The paper aims to discuss these issues. Design/methodology/approach: This paper is a study of the possible effects of alcohol consumption on state financial condition across state governments in the USA, based on a mediation analysis with PROCESS. Findings: This paper finds that there is a significant mediated effect of alcohol consumption on state financial condition through some economic and demographic variables. The paper explores these findings as well as future research. Originality/value: This is the first paper that takes an interdisciplinary approach to the social cost and public finance literature with a specific focus on alcohol consumption.